Pengaruh Persepsi Pelayanan, Kepuasan Dan Disiplinterhadap Kualitas Kinerja Pegawai Di Kantor Kelurahan Gamtufkangen Kecamatan Tidore Kota Tidore Kepulauan - Balqis, Putri (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to determine the effect of perceived service, satisfaction and work discipline on the quality of employee performance. The population in this study is the total population of the community in Gamtufkange Village, Tidore Subdistrict, Tidore City, Tidore Islands as many as 1,940. The type of research conducted is a quantitative approach with a sample of 95 people taken with the Probability Sampling technique. The analysis method used in this research is quantitative analysis with the help of the SPSS 23 application program. The results showed that Service Perception has a positive and significant effect on Employee Performance. Perceived Satisfaction has a positive and significant effect on Employee Performance. Perception of Work Discipline has no positive and significant effect on Employee Performance